Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Penggunaan Obat Pasien Diabetes Mellitus Tipe 2 di Rumah Sakit PMI Kota Bogor: Factor Analysis That Affecting Drug Complience of Type 2 Diabetes Mellitus Patients in PMI Hospital, Bogor - Astri Harsono Putri; Lusi Agus Setiani; Naufal Muharram Nurdin (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Type 2 diabetes mellitus is insulin resistance with a relative of insulin secretion disorders. The prevalence of diabetes mellitus in Indonesia in 2000 came in fourth place by 8,4 million population and in 2030 is estimated to have increased by 2,3 million. This study aims to evaluate medication adherence and factors related to adherence in type 2 diabetes mellitus. This study uses descriptive analysis design conducted in February to March 2020 with a total 60 outpatient respondents. Respondent adherence rates were measured using the Morisky Medication Adherence Scale 8 Items (MMAS 8-Items) questionnaire. The significance of the relationship between variables with respondent compliance was measured using Chi-Square. While the dominant factor influencing the respondent?s medication adherence was measured using Binary Logistic Regression. The results of the study prove that the level of adherence of people with type 2 diabetes mellitus outpatient in the Bogor City PMI is in the category of ?moderate adherence?. Bivariate analysis results showed a significant relationship between education (p value 0,041), the amount of non-diabetic drugs (p value 0,035) and the total amount of drugs (p value 0,003) with respondent adherence. The results of multivariate analysis showed that the variable total amount of drugs was the dominant factor affecting the adherence of respondent taking medication (Odds Ratio 8,350).